Significantly Enhanced Structural, Dielectric and Impedance Properties of BCZT-BFO Sensors - Habib, Muhammad Salman; Rafiq, Muhammad Asif; Maqbool, Adnan (Journal of Sustainable Materials Processing and Management, 2022)
Multiferroics like [(Ba0.85Ca0.15) (Zr0.1Ti0.9) O3, BCZT] and (BiFeO3, BFO) with stochiometric amount wereprepared mixed oxide solid state route adding CuO. The compositions wereconfirmed by X-ray diffraction technique, FTIR confirmed the formation of bonds and the clear ideaof bonding pairs, FESEM supportedthe resultsof microstructure, and it was revealed that the addition of CuO increasedthe densification while it was also served as a sintering agent. The impedance spectroscopy (IS) wasthe tool that explain the relaxation phenomenon of the composition making agreements with the conduction mechanism that the material can be used as negative temperature coefficient of resistance (NTCR) for the applications of capacitors, sensors, actuators,and energy devices.